TWO ACTIVE STAGES OF THE AMBROSIA BEETLE, Platypus quercivorus MURAYAMA ESTIMATED FROM FRASS PRODUCTION - Tarno, Hagus; Qi, Hongye; Kobayashi, Masahide; Futai, Kazuyoshi (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
Beetle activity deep inside wood was studied in field (Mt. Yoshida, Kyoto) and laboratory conditions by monitoring the type and amount of frass ejected from beetle galleries of Platypus quercivorus. Twenty-one galleries were selected from five infested Quercus serrata trees for field studies. In the laboratory, frass production was monitored for three galleries using a computer-aided electrical balance (A&D Co. Ltd.). Long-term patterns of frass production from field observation revealed that there are three distinguishable stages; a fibrous frass stage, an intermediate stage, and a powdery frass stage. The duration of the fibrous frass production was clearly different between galleries, ranging from five to twenty one days. The intermediate stage was also different from gallery to gallery, ranging from two to twenty days. Accordingly, the starting time of the third stage, powdery frass production, ranged from the 19th to the 27th day. Under laboratory conditions, the long-term patterns of frass production revealed that in galleries of logs no. 1 and 2 the fibrous frass period was stopped on the 23rd and 22nd day, respectively. Field monitoring revealed there was a negative relationship between the length of fibrous frass stage and the length of the intermediate stage. Â Keywords: Â fibrous frass stage, Â intermediate stage, Platypus quercivorus, powdery frass stage